Skills for green jobs : country report Germany - (:unkn) unknown (ILO, 2010)
This report "aims to illustrate how greening of the economy, as a result of environmental protection measures, has driven the growth of green skills and green jobs in Germany. [...] Using desk research and interviews, the German response to greening, with the main emphasis on skills responses, are illustrated and assessed, particularly through the use of eight case studies. These case studies give practical insights into the greening process of both existing occupations as well as through the creation of new occupations. A key finding from Germany is that rather than creating new, specific 'green' occupations, many occupations and training curricula have been adjusted and refined to take account of the skills needs of increasingly green aspects of mainstream industry and business as well as eco-industries." (Hrsg., BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; S 6.4.8.1 Umweltberufe; T 3 Forschungsmethoden; I 2.1 Deutschland; Umweltberuf; Qualifikationsbedarf; Qualifikationsanforderung; Qualifikationsanpassung; Früherkennung; Neue Tätigkeitsfelder; Neuer Beruf; Klimaschutz; Erneuerbare Energie; Fallstudie; Bundesrepublik Deutschland